Features that hindered the capacity development of a national prostate cancer service - Ward, Ashleigh Lauren; Cruickshank, Susanne; Forbat, Liz (Frontiers in Health Services, 2023)
Introduction In Scotland, prostate cancer services have struggled to meet demand, and urological cancer services have missed Scottish Government waiting time targets to a greater extent than other cancer services. This study provides understanding of the capacity development needs of a national prostate cancer service including why the service had been unable to adapt to meet demand and how capacity could be developed. Methods Delphi technique was applied to a purposive sample of prostate cancer clinicians working across Scotland between 2015 and 2017. Interviews were conducted with healthcare professionals involved in delivery of care to people with prostate cancer including General Practitioners, followed by questionnaires which were distributed to Specialist Nurses, Oncologists and Urologists involved in delivering specialist prostate cancer services within NHS Scotland. Findings are reported from interviews analysed using a directed approach to content analysis, followed by three rounds of iterative online questionnaires analysed using descriptive statistics. Results Reform is needed to meet demand within prostate cancer services in Scotland. Barriers to capacity development included: lack of shared understanding of quality of care between policy makers and healthcare professionals; lack of leadership of service developments nationally and regionally; and difficulties in drawing on other capacities to support the service. Cohesive working and a need for efficient training for nurse specialists were needed to develop capacity. Consensus was reached for development of national working groups to set standards for quality care (100% agreement) and further development of existing regional working groups (100% agreement) to implement this care (91% agreement), which should include input from primary and community care practitioners (100% agreement) to meet demand. Discussion This work provides important understanding of barriers and facilitators to service development across a national service, including highlighting the importance of a shared vision for quality care between policy makers and healthcare professionals. Mechanisms to support service change are identified.